Green Line Calgary: Integrating Pedestrian LRT Crossings into Our Communities (breakout presentation). (December 2017) - Merchant, Alisha; Oliver, Stephen
Abstract : Calgary's Green Line Light Rail Transit (LRT) program is more than a transit project; it will improve the way Calgarians live, work, and move around the city by creating sustainable, liveable, and vibrant communities. The Green Line will integrate Low Floor LRT (LFLRT) into Calgary communities to provide enhanced transit service and support dramatic mode split changes in key areas of the city. This unique project focuses on fostering pedestrian and cycling connectivity, improving existing urban realm, and potential for future Transit Oriented Developments (TOD) integration. As the Green Line progresses through existing communities and future TOD areas, a strong focus on pedestrian connectivity to/from stations and across the LRT is essential. In creating connections, emphasis was placed on creating safe, convenient, and effective crossings for all transit users, and minimizing physical impacts/disruption to adjacent communities. This paper provides an overview of collaborative design processes used in enhancing the walking and cycling environment at key intersections along the Green Line, deviating from the City's traditional approach. This includes both a description of the consensus building process, the extensive research completed and the preferred design treatments that were developed. Challenges encountered in creating pedestrian connections included working within limited road right-of-way, avoiding the LRT's dynamic envelope, and maintaining cross-street access for large vehicles utilizing the corridor. Following extensive research, collaboration, and constructive workshop discussions with city staff from multiple disciplines, architects, and engineering consultants, pedestrian crossing treatments for each intersection type were narrowed. Each intersection type received stakeholder consensus on best possible LRT crossing treatments. This paper presents crossing treatments developed including M-crossings, Z-Crossings, smart right medians, raised crosswalks, and truck aprons. As transportation authorities worldwide invest in LFLRT systems, understanding challenges in facilitating safe, comfortable, and equitable pedestrian crossings is critical. This paper entails lessons learned, best practices, and suggested design treatments to achieve enhanced pedestrian accommodation with new LRT construction.